2009
DOI: 10.1002/pon.1559
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the 3‐factor model and structural invariance across racial/ethnic groups for the FACIT‐Sp: a report from the American Cancer Society's Study of Cancer Survivors‐II (SCS‐II)

Abstract: The 3-factor model is likely to provide more specific information for studies in the field. In the construction of scales for use with diverse samples, researchers need to pay greater attention to racial/ethnic differences in interpretation of items.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
4
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(176 citation statements)
references
References 30 publications
19
149
4
4
Order By: Relevance
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…41 This positive association was consistent for overall QOL (ranges from 0.49 to 0.70) and for physical (ranges from 0.25 to 0.28) and mental health (ranges from 0.55 to 0.73). 10,20,24,26 The correlation between Meaning/ Peace and mental health was found to be stronger than physical health in three studies, 11,29,45 although not for 288 BAI AND LAZENBY 2. FACIT-Sp-12 and two subscales remained independent predictors of total FACT-G controlling for demographic and clinical characteristics.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 99%
“…[24][25][26][27][28] Sample size ranged from 44 18 to 8805. 29 Thirteen studies conducted in the United States had a significant proportion of subjects that belong to racial, ethnic, or religious minorities. 10,14,15,[20][21][22][23][24][25][30][31][32][33] Eight studies targeted breast, 19,32,34,35 prostate, 30,31 or colorectal cancer patients 15 only.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations